Regional movement patterns of a small‐bodied shark revealed by stable‐isotope analysis. Issue 5 (7th April 2015) - Munroe, S. E. M.; Heupel, M. R.; Fisk, A. T.; Logan, M.; Simpfendorfer, C. A.
<x xml:space="preserve">Abstract</x> This study used stable‐isotope analysis to define the nearshore regional residency and movements of the small‐bodied Australian sharpnose shark Rhizoprionodon taylori. Plasma and muscle δ13C and δ15N of R. taylori were collected from across five embayments and compared with values of seagrass and plankton from each bay. Linear distances between adjacent bays ranged from 30 to 150 km. There was a positive geographic correlation between R. taylori tissue and environmental δ13C values. Populations with the highest tissue δ15N were collected from bays that had the highest environmental δ15N values. These results suggest that R. taylori did not forage more than 100 km away from their capture location within 6 months to 1 year. The successful application of isotope analysis to define R. taylori movement demonstrates that this technique may be used in addition to traditional methods to study the movement of sharks, even within similar habitats across regionally small spatial scales (<100 km).